Experimental study on flow-induced motions of TLP focusing on effects of appendages and mass ratio. (15th January 2020) - Tian, Chenling; Liu, Mingyue; Xiao, Longfei; Wang, Shisheng; Lu, Haining
Abstract: Flow-induced motion (FIM) is an important issue for deep-draft floating platforms, reducing the fatigue life of mooring and riser systems. Tension leg platforms (TLPs) with a smaller mass ratio ( m r, the ratio of the platform mass to the displacement), may experience more pronounced FIM responses in current. To investigate the FIM behavior of TLPs in towing tests, this research adopts an air-bearing system, mainly composed of low-friction air bearings and a smooth flat plate, to accurately simulate the mass ratio. The results demonstrated that in the range of 0 . 64 ≤ m r ≤ 0 . 90, the transverse amplitudes did not decrease with an increase in the mass ratio because the Scruton number S c did not exceed 0.1. Through model tests, the effect of appendages on the FIM of TLPs was also examined. The results of the screening tests from 0 ∘ to 360 ∘ with an interval of 22.5 ∘ indicated that the transverse response is characterized by symmetry with a cycle of 90 ∘, while the yaw motion exhibits asymmetry owing to the effect of appendages. The largest transverse amplitude was obtained at 90 ∘, with a value of A y ∕ D = 0 . 408 occurring at U r = 7 . In comparison with the bare hull platform, the transverse amplitude of the TLP with appendages significantly decreased by approximately 82% in the range of 6 ≤ U r ≤ 8 at 45 ∘ . Overall, these substantial results are expected to improve the understanding of the FIM characteristics of TLPs, and to provide benchmark data for design and numerical prediction as well. Highlights: Effects of appendages and mass ratio on the FIM of a TLP are investigated experimentally. Motion responses, excitation loads, and spectral characteristics are discussed. Transverse motions are characterized by symmetry for the cycle of 90 ∘ . The yaw motions exhibit an asymmetry owing to the effect of appendages. The effect of mass ratios on the FIM of TLP does not show regular pattern owing to the Scruton number lower than 0.1.